PENGARUH BONUS PLAN TERHADAP RESPON PASAR DENGAN INCOME SMOOTHING SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2021-2023 - Ria Lusiana; Marhaendra Kusuma; Imarotus Suaidah (CV. Denasya Smart Publisher, 2025)
This study aims to examine the effect of bonus plans on market response with income smoothing as a mediating variable in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The novelty of this research lies in the inclusion of income smoothing as a mediating variable. The bonus plan variable is proxied by the natural logarithm of salary expenses, income smoothing is measured using the Eckel index, and market response is measured using stock returns. This research uses secondary data obtained from the IDX website in the form of annual financial reports and daily stock prices. The sample consists of 19 banking companies listed on the IDX. This is a quantitative study using path analysis as the analytical technique. The findings show that, on average, banking companies engage in income smoothing. The results indicate that the bonus plan has a positive effect on market response, the bonus plan has a positive effect on income smoothing, income smoothing has no significant effect on market response, and income smoothing does not mediate the relationship between the bonus plan and market response.